Verify the following:
(i) (-14) (-8) = (-8) X (-14)
(iii) (-10) I(-7)+(-9)} = ((-10) (-7)+ (-10) × (-9)}
(ii) ((-7)

Question

Verify the following:
(i) (-14) (-8) = (-8) X (-14)
(iii) (-10) I(-7)+(-9)} = ((-10) (-7)+ (-10) × (-9)}
(ii) ((-7) ~ 5) (-6) = (-7) > {5 × (-6)}​

in progress 0
Serenity 4 months 2021-07-06T15:26:48+00:00 1 Answers 0 views 0

Answers ( )

    0
    2021-07-06T15:27:56+00:00

    Step-by-step explanation:

    i. -14*-8 = -8 * -14. (associatve

    112 = 112

    hence proved

Leave an answer

Browse

9:3-3+1x3-4:2 = ? ( )